Effect-directed analysis of estrogenic chemicals in sediments from an electronic-waste recycling area. (1st August 2022) - Ma, Qianchi; Yang, Xiaoxi; Guo, Yunhe; Wang, Yi; Liu, Yanna; Zhang, Songyan; Xie, Heidi Qunhui; Xiang, Tongtong; Li, Zikang; Nie, Tong; Yan, Yuhao; Qu, Guangbo; et al.
Abstract: Electronic waste (e-waste) pollution is of great concern due to the release of hazardous chemicals during the improper e-waste disposal. Many chemicals leached from e-waste were reported to pose estrogenic effects. To date, little is known regarding the occurrence and biological effects of estrogenic chemicals in sediments near an e-waste area. In this study, an effect-directed analysis (EDA) is applied to determine the estrogenic chemicals in sediments of four sites collected from a typical e-waste recycling city in China. Following screening with the ER-CALUX assay, the extract of sample with the most potent effect was subjected in fractionation using reverse phase liquid chromatography. Based on a target analysis for the active fractions, four compounds, including estrone, 17 β -estradiol, 17 α -ethinylestradiol and bisphenol A, were identified, and these contributed to 17% of the total toxic effects in the sample. A further nontarget analysis screened four candidates, namely diethylstilbestrol (DES), hexestrol (HES), nandrolone and durabolin, and the total contribution was found to be 48% from the active sample. Specifically, DES and HES were only detected in the active sample and were found to be the primary drivers of estrogenic effects. An examination of the identified chemicals in the four sites indicated that these estrogenic chemicals may originate from e-waste recycling, livestock excretion and domestic waste. These findings uncovered the estrogenic pollutants in sediments from an e-waste area. Considering single endpoint in biological assay is not abundant to screen chemicals with different toxic effects, further EDA studies with multiple endpoints are required to better understand the occurrence of representative or unknown chemicals in e-waste-polluted areas. Graphical abstract: Image 1 Highlights: Effect-directed analysis was used to identify estrogenic compounds in sediments. Diethylstilbestrol and hexestrol were identified as primary estrogenic chemicals. The contamination of estrogenic chemicals was point-specific. Estrogenic chemicals may originate from excrement, domestic waste and e-waste.